P–487 Couples undergoing first level assisted reproductive techniques: An Actor-Partner interdependence model of dyadic adjustment, psychological symptoms, alexithymia and romantic attachment on body-image avoidance. (6th August 2021) - Mancinelli, E; Salcuni, S; Muratti, A; Grillo, A; Alessi, C; Guglielmino, A; Finos, L
Abstract: Study question: The study aims to assess the commonalities and interdependence of couples undergoing first-level Assisted Reproductive Techniques (ART) as regards body-image avoidance referred to body-image dissatisfaction. Summary answer: Partners' functioning seem specular yet not interdependent, as not showing a couple-as-a-unit modality of functioning. Body-image avoidance is only influenced by intra-personal variables. What is known already: Stressful bodily emotions and body perception related to infertility and ART are critical aspects for people desiring having children. Infertility undermines women's self-esteem and body-image, damaging their self-identity as women, while in males infertility associates with body dissatisfaction referring to perceived reduced physical fitness and personal failure, thus undermining their body virility. For infertile women, body-image dissatisfaction associates with reduced marital adjustment, and vice-versa; yet no study has considered how males body-image dissatisfaction associates with marital satisfaction. Nonetheless, couples should be considered as a unit, considering that infertile couples' adjustment is influenced by their own, and their partners', perceived stress. Study design, size, duration: The study follows a cross-sectional design and is part of an ongoing transversal and longitudinal project, started in 2012, investigating the well-being of couples undergoing ART. For the present study only a minority of the existing data were considered, thus only including couples at the first level of ART with the intent of investigating couples' commonalities and interdependence before treatments pervasiveness increases. Participants/materials, setting, methods: Minimum N = 79 couples needed to be considered according to Power analysis results. N = 118 couples aged 24 to 46 years (women Mage=34.92, SD = 3.98; men Mage=37.45, SD = 5.25) were included, and declaring trying to get pregnant from 1 to 8 years (M = 3.18; SD = 1.99) and to never had children, although 22.9% of women had at least an abortion. Participants completed the Body-Image Avoidance Questionnaire, Toronto Alexithymia Scale–20, Dyadic Adjustment Scale, Symptom Checklist–90-Revised and Experiences in Close Relationships Scale-Revised. Main results and the role of chance: The sample presents non-clinical levels of functioning referring to their psychological symptoms, alexithymia and body-image avoidance. Multivariate rank tests show that females report significantly higher levels of body-image avoidance (stat=–5.73; adj.p=.001), psychological symptoms (stat=–4.58; adj.p=.001) and romantic anxious attachment (stat=–3.33; adj.p=.005). These differences were confirmed also after applying multiplicity control. Moreover, bi-variate Pearson's r correlations show an association among partners' dyadic adjustment (r=.293; p<.001), albeit their overall level of dyadic adjustment is low. Significant correlations among partners also emerged as regards psychological symptoms (r=.258; p<.001) and alexithymia (r=.16; p=.05). The couple-effect, thus considering the couple as the unit of analysis, was modeled through an Actor-Partner Interdependence Model. For both partners, dyadic adjustment's actor-effect associates with body-image avoidance (women: β = 0.133, p=.026; man: β = 0.133, p=.026). Furthermore, for both men and women, psychological symptoms' actor-effect associate to body-image avoidance (women: β = 0.467, p<.00; men: β = 0.499, p=.001). Comparing the level of influence of actor and partner effects among partners, the psychological symptoms' actor effect results significantly more influential than the partner-effect (women: Δ = 0.378, p=.015; men: Δ = 0.587, p=.001). Only for males, alexithymia's actor effect is significant (β = 0.499; p=.001). Limitations, reasons for caution: Results should be considered in light of some limitations. Specifically, the cross-sectional study design, lack of a control group with no infertility issues, the use of self-report measures, homogeneity among couples and the sample small sample size (although sample size was appropriate to retain a power of at least .8). Wider implications of the findings: Results support the differentiation of gender-specific psychosocial interventions along the ART path, preventing and mitigating the negative impact of infertility and ART on body-image dissatisfaction and avoidance and on the couples' well-being. Trial registration number: Not applicable